Novos corantes moleculares derivados de sulfetos vinílicos: síntese e propriedades fotofísicas - Araujo, Matias Monçalves (2017)
This thesis describes, initially, the synthesis and photophysical characterization of new sulfides,sulphoxides and vinyl sulfones based dyes. The compounds in question were obtained in good yields and good diastereoselectivity through Horner-Wadsworth- Emmons (HWE) reactions. The compounds absorb light in the UV/Vis region, with the major transitions occurring between – * orbitals. As for the emission, the PS-1 and PS- 2 vinyl sulphides have their maximum emission bands in the blue region of the spectrum. The oxidation to their respective sulphoxides and sulfones, and the attainment of D– –A structure, causes the emission to undergo a bathochromic shift to the green region of the spectrum. These effects are most pronounced in the triphenylamine derivatives (PSO-1 and PSO2-1) and in polar solvents (positive solvatocromism). With the aid of DFT and TD-DFT calculations, it can be observed that this behaviors are related to the formation of intramolecular charge transfer states (ICT) in the excited state. Subsequently, the design, synthesis and characterization of new vinyl sulphides for possible application in dye-sensitized solar cell (DSSCs) are presented. The compounds were designed to have a D– –A structure, where the sulphides would serve as a bridge between the donor (D) and acceptor (A) blocks. The compounds studied were obtained by the HWE and Knoevenagel condensation, in good yields and good diastereoselectivity. Through preliminary photophysical analysis, it has been observed that the dyes have a wide light absorption range (250–550 nm), in particular the dyes derived from malononitrile PCN-1, PCN-2 and PSCN. In addition to being greatly influenced by the nature of the electron acceptor group. These characteristics are in line with that expected for application in DSSCs and are similar to several sensitizing dyes reported in the literature.